A argumentação em questões sociocientíficas na formação inicial de professores de ciências: o caso do xenotransplante - Idalino, Rosane Karine Tavares (2021)
From the beginning of the twentieth century, many studies in science education amass sought strategies that enable the training of the learners and teachers capable of making informed and informed decision making. Socioscientific issues (SSI), due to their controversial identity and because they encompass social issues, are pointed out as potentializers, both in the era of arguments as nicely as in the production of evidence of ethical and moral development. One of these SSI that can be worked in science classes is xenotransplantation, that is, organ or tissue transplantation from non-human animals to humans. The goal of this research is to identify the argumentative skills and possible ethical connections of science undergraduates regarding SSI xenotransplantation. As a methodology, the present work has a qualitative nature. The target audience was science teachers in initial workout at the Professor Alberto Carvalho University Campus / UFS, placed in the city of Itabaiana. Data collection was carried out through focus groups, their analyzes were made through the argumentative diagram, proposed by Toulmin (2006) and the possible ethical and moral aspects according to the main ethical aspects. From the analysis of the results, it was establish that the science undergraduates organized to elaborate arguments, however, according to Toulmin's argumentative layout, the arguments elaborated presented a simple arrangement, with few elements. With regard to ethical commitment, there was a predominance of hedonistic and utilitarian ethics, respectively. Respecting the socioscientific question of xenotransplantation, it proved to be a productive promoter of debate